Analisis Pengaruh Kualitas Pelayanan, Harga, dan Promosi terhadap Keputusan Pembelian pada E-Commerce Shopee - Witarisma , Silvana Widya (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2021)
Improvements in the field of technology increasingly show very fast progress where all daily activities that are carried out can all be done easily and quickly using only internet access. Changes in behavior that occur in the community in e-commerce is a challenge for companies to be able to meet the needs and desires of their consumers. One of the online applications that implements the largest e-commerce concept in Indonesia is Shopee. The increase in Shopee users affects the purchase rate. So the purpose of this study is to find out whether service quality, price, and promotion affect purchasing decisions by Shopee consumers at Karang Taruna members in Ngangkatan Village, Rejoso District, Nganjuk Regency. The research method used in this research is using quantitative research methods. With a population of 71 members of the Youth Organization, and the sample is 45. The results show that simultaneously Service Quality, Price, and Promotion have a significant effect on purchasing decisions. Keywords: Quality of service, Price, Promotion, Purchase Decision